Enhance work for java based network analyzer tool used to analyze network simulator files - Jawad Alkenani; Khulood Ahmed Nassar (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
The network performance measurement is important in computer networks, and performance measurement may not be effective for installation in peripheral devices resulting in the replacement of those devices and thus increasing cost. In light of this, it is better to have a simulation of the network to see its performance rather than the actual design. NS-2 is one of the most popular and widely used open-source network simulators in many organizations, which generates trace files during the simulation experience. The trace file contains all network events that can be used to calculate performance. Thus, NS-2 does not offer any visualization options for analyzing simulation results (trace files), which is the fundamental problem of trace file parsing difficulty. This paper provides a graphical user interface tool that enables researchers to quickly and efficiently analyze and visualize NS-2 trace files. This tool is a development of the JDNA tool, as it could not analyze more than one trace file at a time. In addition, this work can be a useful guide for network researchers or other programmers to analyze their networks and understand how to calculate network performance metrics.